Editorial: New Trends in Connectomics - Olaf Sporns; Danielle S. Bassett (Network Neuroscience, 2018)
Connectomics is an integral part of network neuroscience. The field has undergone rapid expansion over recent years and increasingly involves a blend of experimental and computational approaches to brain connectivity. This Focus Feature on “New Trends in Connectomics” aims to track the progress of the field and its many applications across different neurobiological systems and species.